Le développement du pouvoir agir, l’agentivité et le sentiment d’efficacité personnelle des jeunes face aux problématiques sociales et environnementales : apports conceptuels pour un agir ensemble - Émilie Morin; Geneviève Therriault; Barbara Bader (Éducation et Socialisation)
To cope with complex environmental issues that have a direct impact on cultural and natural environments, education for empowerment seems to be an unavoidable avenue (Schreiner, Henriksen & Kirkeby Hansen, 2005). However, to allow transformations in terms of educational discourses and practices, it seems necessary to clarify and define the limits of the conceptual tools identified as relevant by researchers in the field (Stevenson, Brody, Dillon & Wals, 2013). In this article, inspired be the theoretical frame of a doctoral research in progress, the concepts of empowerment, agency and self-efficacy beliefs will be further explored. They will then be connected to highlight the concept of sense of empowerment for a transformative and critical environmental education.